2019
DOI: 10.1016/j.neuron.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Rules of Spike Train Decoding Revealed at the Sensitivity Limit of Vision

Abstract: All sensory information is encoded in neural spike trains. It is unknown how the brain utilizes this neural code to drive behavior. Here, we unravel the decoding rules of the brain at the most elementary level by linking behavioral decisions to retinal output signals in a single-photon detection task. A transgenic mouse line allowed us to separate the two primary retinal outputs, ON and OFF pathways, carrying information about photon absorptions as increases and decreases in spiking, respectively. We measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
106
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(122 citation statements)
references
References 54 publications
(74 reference statements)
14
106
2
Order By: Relevance
“…Several studies showed that the brain might not be able to make the best use of all the signals coming from the different cell types [28,29]. However, recent works (see, for example, [30]) have shown that neurons might integrate the output of several cell types together, as early as in the LGN.…”
Section: Limits Of the Ideal Observer Analysismentioning
confidence: 99%
“…Several studies showed that the brain might not be able to make the best use of all the signals coming from the different cell types [28,29]. However, recent works (see, for example, [30]) have shown that neurons might integrate the output of several cell types together, as early as in the LGN.…”
Section: Limits Of the Ideal Observer Analysismentioning
confidence: 99%
“…We did so by creating a movie ( Supplementary Movie 2) where we applied a sinusoidal change to individual shape parameters in equation 3. In this way, at any given time and for the ℎ eigenpose, the mouse body could be described as ( ) = ̅ + √6sin (2 ) • . By looking at the movie it is apparent that each eigenpose captures coordinated changes in the distances between body landmarks and angles between head and body.…”
Section: Interpretation Of the Eigenposesmentioning
confidence: 99%
“…For this analysis the response matrix encompassed an epoch starting 0.33s before the stimulus onset and ending 2s after the onset. Since both the number of clusters and the duration of the primitive was unknown we repeated the clustering for a range of [2,10] clusters and for six different durations (0.133s, 0.2s, 0.333s, 0.4s, 0.666s and 1s). In order to model arbitrarily (finite) long ` temporal relations between subsequent primitives occurring on the same trial we used Variable-order Markov Models (VMMs, [62,63]).…”
Section: Analysis Of Behavioural Primitivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three GC types in the mouse retina receive input from the RB pathway at or near visual threshold: the ON α GC and the OFF α and δ GCs, which exhibit high sensitivity to spatial contrast in the visual scene—similar to primate parasol cells —and project to the geniculo-cortical pathway (Ala-Laurila et al, 2011; Ala-Laurila and Rieke, 2014; Dunn et al, 2006; Grimes et al, 2018a; Grimes et al, 2015; Grimes et al, 2014b; Grimes et al, 2018b; Ke et al, 2014; Kuo et al, 2016; Murphy and Rieke, 2006, 2008). Input from the RB pathway to ON α GCs provides the signal that guides behavior at visual threshold (Smeds et al, 2019).…”
Section: Introductionmentioning
confidence: 99%